Environmental changes and general health condition (Journal of Preventive and Social Medicine, 2021)
Background: The environment directly affects health status and plays a major role in quality of life, years of healthy life lived, and health disparities. Humans impact the physical environment in many ways, like over population, pollution, burning fossil fuels, and deforestation. The study was conducted to assess environmental changes and the general health condition.Methods: It was a cross-sectional study. To assess environmental  changes  and  general  health  condition of dental second year student and data were collected by checklist. Respondents were selected purposively. Data were collected on 8th September 2019 at Marks medical college dental unit. Samples were second year dental students, who were presented in class on that date.Results: Distribution of the respondents according to sex, 64.5% were female and 35.5% male.  Majority  of the student (51.6%) were come from outside of the Dhaka. 45.2% respondents were lived in Dhaka by born. 80.6% respondents lived with their family. It was alarming that 83.9% respondents never did physical exercise and only 16.1% did sometimes physical exercise. 61.3% respondent admired that they have hair loss, 16.1% has no problems in skin but others has problems. 51 .6% has dust, 1 2.9% has food allergy. 6.5 % has frequently exposure of diarrhea diseases. Often 67.7% has been suffered by headache. Reason of seasonal changes  29%  respondents suffered by itching. 77.4% and 83 .9% respondents were affected by anxiety and depression. 77.4% respondent has knowledge about weather change in our country as well as whole world.Conclusion: General health condition maybe changed for multiple causes. Environment is one of the strong factors. The relation between environmental temperature and health has been known for a very long time.JOPSOM 2020; 39(1): 73-77